Recent advances in understanding the human host immune response in tuberculous meningitis - Barnacle, James R.; Davis, Angharad G.; Wilkinson, Robert J. (Frontiers in Immunology, 2024)
Tuberculous meningitis (TBM), the most severe form of tuberculosis, causes death in approximately 25% cases despite antibiotic therapy, and half of survivors are left with neurological disability. Mortality and morbidity are contributed to by a dysregulated immune response, and adjunctive host-directed therapies are required to modulate this response and improve outcomes. Developing such therapies relies on improved understanding of the host immune response to TBM. The historical challenges in TBM research of limited in vivo and in vitro models have been partially overcome by recent developments in proteomics, transcriptomics, and metabolomics, and the use of these technologies in nested substudies of large clinical trials. We review the current understanding of the human immune response in TBM. We begin with M. tuberculosis entry into the central nervous system (CNS), microglial infection and blood-brain and other CNS barrier dysfunction. We then outline the innate response, including the early cytokine response, role of canonical and non-canonical inflammasomes, eicosanoids and specialised pro-resolving mediators. Next, we review the adaptive response including T cells, microRNAs and B cells, followed by the role of the glutamate-GABA neurotransmitter cycle and the tryptophan pathway. We discuss host genetic immune factors, differences between adults and children, paradoxical reaction, and the impact of HIV-1 co-infection including immune reconstitution inflammatory syndrome. Promising immunomodulatory therapies, research gaps, ongoing challenges and future paths are discussed.